Mapping bias: A rhizomatic critique of the National Literacy Panel Report. Issue 2 (3rd April 2021) - Cole, Mikel W.; David, Samuel
ABSTRACT: The Report of the National Literacy Panel on Language-Minority Children and Youth was designed to be a definitive review of research on the literacy development of language-minoritized students. We adopt conceptual methods from rhizomatic mapping to replicate the report's literature searches and critically examine studies eliminated based on the panel's inclusion criteria. Our analyses demonstrate that epistemological bias disproportionately excluded small-scale, qualitative studies, and mapping citation patterns of scholarly impact demonstrates ongoing stratification and territorialization of scholarship since the report was published.